Maternal and infant antiretroviral therapy adherence among women living with HIV in rural South Africa: a cluster randomised trial of the role of male partner participation on adherence and PMTCT uptake - Deborah L. Jones; Violeta J. Rodriguez; Manasi Soni Parrish; Tae Kyoung Lee; Stephen M. Weiss; Shandir Ramlagan; Karl Peltzer (Taylor & Francis Group, 2021)
'Mother-to-child transmission of HIV' can occur during the period of pregnancy, childbirth, or breastfeeding. 'Prevention of mother-to-child transmission of HIV' (PMTCT) in Mpumalanga Province, South Africa, is especially vital as the prevalence of HIV is 28.2% in women aged 15-49. PMTCT interventions resulted in a drop of MTCT rates in Mpumalanga from ∼2% in 2015 to 1.3% in 2016. This randomised controlled trial in Mpumalanga examined the potential impact of a lay healthcare worker administered intervention, 'Protect Your Family', on maternal and infant adherence, and to assess the relative influence of male partner involvement on infant and maternal adherence. This cluster randomised controlled trial used a two-phase and two-condition (experimental or control) study design where participants (n = 1399) did assessments both during pregnancy and post-postpartum. Only women participated in Phase 1, and both female and male partners participated in Phase 2. Results indicated that male involvement was associated with self-reported maternal or infant antiretroviral therapy (ART) adherence, but the intervention was not associated with ART adherence. Self-reported adherence was associated with depression, age, and partner HIV status. The study results provide support for the involvement of men in the antenatal clinic setting during pregnancy. Results also support further research on the meaning and assessment of male involvement and clarification of the constructs underlying the concept in the sub-Saharan African context. Outcomes provide support for male involvement and treatment of depression as adjuncts to improve uptake of both maternal and infant medication as part of the PMTCT protocol.